Primary Perivascular Epithelioid Cell Tumor of the Lung: A Case Report - Hye Rim Na; Jong Hui Suh; Jiyun Lee (Journal of Chest Surgery, 2023)
Perivascular epithelioid cell tumors (PEComas) are very rare mesenchymal neoplasms, composed of histologically and immunohistochemically distinctive cells that form a sheetlike appearance around vessel lumens. Although most are benign, a malignant subset does exist, complicating clinical diagnostic efforts. Proper evaluation and management are thus essential for long-term patient survival. Herein, we present a rare case of a benign pulmonary PEComa that was diagnosed postoperatively in a 45-year-old woman.